Defect engineering as a versatile route to estimate various scattering mechanisms in monolayer graphene on solid substrates. Issue 38 (15th September 2015) - Srivastava, Pawan Kumar; Ghosh, Subhasis
Abstract : By correlating Raman spectra and electrical measurements, we demonstrate that defect-engineering can be used to estimate various possible scatterers in graphene monolayers on solid substrates. Abstract : It is known that the experimental conditions and growth methods determine the different carrier scatterings responsible for large variation of carrier mobility in graphene monolayers. Here we present a systematic investigation on various possible scattering mechanisms responsible for limiting the carrier mobility in graphene on a solid substrate, like SiO2 . This has been possible by defect engineering in graphene monolayers obtained by liquid phase exfoliation of graphite in polar and non-polar solvents with the dielectric constant varying from 2.5 to 64. Lattice defects in graphene monolayers have been characterized by scanning tunnelling microscopy and Raman spectroscopy. Correlation between the results obtained from electrical measurements and the information obtained from Raman spectra have revealed different scattering mechanisms responsible for deciding the carrier mobility. It has been shown that remote interfacial phonons in SiO2 are responsible for limiting the carrier mobility at room temperature whereas, substrate impurities and Raman active point defects in the graphene lattice are the dominant scatterers for limiting the mobility at low temperatures.